Voices from The Classroom : Teachers’ and Students’ Perceptions of Using SPS-Based Worksheets to Promote HOTS in Science Learning (A Needs Analysis) - Widia, Syarifah; Evendi, Evendi; Halim, A. (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to analyze the needs for developing Student Worksheets that support Higher Order Thinking Skills (HOTS) and Science Process Skills (SPS) in science learning. A descriptive qualitative approach was employed in this study, where data were collected from 56 students and 3 science teachers across two schools in Banda Aceh, which were purposefully selected to examine the implementation of SPS-based worksheets in school located in the both urban and rural setting using structured questionnaires. The needs analysis was guided by the framework proposed by Hutchinson & Waters, focusing on three key elements: necessities, lacks, and wants. The findings indicate that both teachers and students recognize the importance of SPS-based worksheets in developing HOTS. Necessities include worksheets that support HOTS, especially in practical activities. However, there is a lack of SPS-based worksheets due to limited time and training and wants reflect teachers’ strong desire for professional development to create such worksheets that can enhance students’ HOTS. However, existing worksheets do not adequately address these needs, particularly in terms of contextualized problems, activity variation, and relevance to real-life situations. The study suggests that there is a pressing need to develop innovative, contextual worksheets integrated with problem-solving strategies. Such worksheets would not only support more meaningful learning but also challenge students cognitively, fostering skills that align with the demands of the 21st century.